Trauma, Surrealism and Time Out of Joint in The Lighthouse - Gerdesits, Pál (AMERICANA E-journal of American Studies in Hungary, 2022)
The main problem of Robert Eggers’ The Lighthouse is the concept of time. Both protagonists of the movie are tied to a certain point of their past via their traumas and this fixation completely sprains their experience of time. In my essay, I demonstrate how this sprain is called to life in the movie and I also point out how the different aspects of interpretation converge in the recurring motif of the mermaid. I also articulate how Eggers uses the tool of “direct aging” to create a unique, time-travelling experience of reception while I demonstrate the most important differences between the concept of nostalgia and trauma.